Ответы и объяснения

Лучший Ответ!
2013-11-14T08:59:41+00:00
Ctg(t-P)=ctg(t)=-3/4

а) cos(3P/2-t)=-sin(t) где P/2<t<P
есть чудо-формула: ctg^2(t)+1=1/sin^2(t)
9/16+1=1/sin^2(t) => 25/16=1/sin^2(t) => sin^2(t)=16/25 => sin(t)=+-4/5
т.к. у нас P/2<t<P ,то ответ sin(t)=4/5, но нам надо найти -sin(t) => -sin(t)=-4/5

б) cos(P+t)=-cos(t) где P/2<t<P
    есть чудо-формула: tg^2(t)+1=1/cos^2(t)
16/9+1=1/cos^2(t) =>  25/9=1/cos^2(t) => cos^2(t)=9/25 => cos(t)=+-3/5 т.к. P/2<t<P 
то cos <0 получаем, что cos(t)=-3/5, но нам надо найти -cos(t) => -cos(t)=3/5